2016
DOI: 10.1002/tal.1279
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of seismic performance factors for self‐centering controlled rocking special concentrically braced frame

Abstract: SUMMARYModern self-centering controlled rocking special concentrically braced frame (SC-CR SCBF) is capable of reducing structural damage compared with conventional buildings following an earthquake. This investigation quantifies three seismic performance factors, including over-strength factor (Ω 0 ), period-based ductility (μ T ) and response modification coefficient (R), for low-and mid-rise SC-CR SCBFs. Nonlinear static analysis is conducted to derive Ω 0 and μ T factors for 12 SC-CR archetypes. Validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
(49 reference statements)
1
20
0
Order By: Relevance
“…The mean value of residual roof drift for the RCBF and RZBF is 0.0014 and 0.00016 radians, which showed the reliable self-centering behavior of these frames. This result is identical with the result of past researches [40,43,44]. They presented that the residual roof drift for fixed base frame is 46 and 54 times larger than the residual roof drift for rocking frame under DBE and MCE earthquakes, respectively.…”
Section: Roof Drift Ratio and Residual Driftsupporting
confidence: 90%
See 1 more Smart Citation
“…The mean value of residual roof drift for the RCBF and RZBF is 0.0014 and 0.00016 radians, which showed the reliable self-centering behavior of these frames. This result is identical with the result of past researches [40,43,44]. They presented that the residual roof drift for fixed base frame is 46 and 54 times larger than the residual roof drift for rocking frame under DBE and MCE earthquakes, respectively.…”
Section: Roof Drift Ratio and Residual Driftsupporting
confidence: 90%
“…Also, RCBF experiences first damage at higher drifts comparing with CBF system, resulting in better seismic performance in terms of drift ratio and residual drift as presented in different experimental and analytical studies [10,40]. Recent studies presented that RCBFs like rocking concentrically braced frame [10,41,42], dual rocking frames [31,43,44], using multiple rocking joint through the height of the frame [11], rocking braced frames with energy dissipating elements and various story numbers [45] and tension-only concentrically braced frames with rocking core [46] are able to decrease damage under severe earthquakes and enhance the seismic performance of ordinary CBFs in terms of uniform distribution of inter story drifts. Huang et al showed that RCBFs are economically better systems comparing to CBFs for low and mid-rise building under severe earthquakes [47].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, self‐centering earthquake‐resisting systems (SC‐ERSs) have been developed to provide a sustainable system through directing seismic damage to replaceable devices. Figure a shows examples of rocking and stepping self‐centering systems including single or coupled stepping braced frames, pin‐supported rocking frame or wall, rocking precast concrete wall, and self‐centering timber frames . These lateral resisting systems are generally composed of bounded or unbounded posttensioning (PT), replaceable energy dissipation (ED) devices, rigid strut beam, bumper, and special diaphragm connections.…”
Section: Introductionmentioning
confidence: 99%
“…Some collapse assessment studies have been completed previously on CRSBFs , which have shown that they can provide acceptable collapse prevention characteristics based on the FEMA P695 methodology . The study by Ma et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some collapse assessment studies have been completed previously on CRSBFs [3,9,10], which have shown that they can provide acceptable collapse prevention characteristics based on the FEMA P695 methodology [11]. The study by Ma et al [3] used an elastic model to evaluate one three-storey building, two six-storey buildings and one nine-storey building with a constant response modification factor of R D 8, and ED and PT parameters selected within a direct displacement-based design framework.…”
Section: Introductionmentioning
confidence: 99%